Global patterns and trends in colorectal cancer incidence and mortality. Issue 4 (27th January 2016) - Arnold, Melina; Sierra, Mónica S; Laversanne, Mathieu; Soerjomataram, Isabelle; Jemal, Ahmedin; Bray, Freddie
Abstract : Objective: The global burden of colorectal cancer (CRC) is expected to increase by 60% to more than 2.2 million new cases and 1.1 million deaths by 2030. In this study, we aim to describe the recent CRC incidence and mortality patterns and trends linking the findings to the prospects of reducing the burden through cancer prevention and care. Design: Estimates of sex-specific CRC incidence and mortality rates in 2012 were extracted from the GLOBOCAN database. Temporal patterns were assessed for 37 countries using data from Cancer Incidence in Five Continents (CI5) volumes I–X and the WHO mortality database. Trends were assessed via the annual percentage change using joinpoint regression and discussed in relation to human development levels. Results: CRC incidence and mortality rates vary up to 10-fold worldwide, with distinct gradients across human development levels, pointing towards widening disparities and an increasing burden in countries in transition. Generally, CRC incidence and mortality rates are still rising rapidly in many low-income and middle-income countries; stabilising or decreasing trends tend to be seen in highly developed countries where rates remain among the highest in the world. Conclusions: Patterns and trends in CRC incidence and mortality correlate with present human development levels and their incremental changes might reflect the adoption of more western lifestyles. Targeted resource-dependent interventions, including primary prevention in low-income, supplemented with early detection in high-income settings, are needed to reduce the number of patients with CRC in future decades.